Private and public families: Social workers’ views on children’s and parents’ position in Chile, England, Lithuania and Norway (Journal of Comparative Social Work, 2019)
EnglishSocial workers around the world work with families and family complexities in their everyday practice. In this cross-national study, we explore social workers’ family intervention practices related to family definitions and functions, and how social workers balance children’s and parents’ rights and social policies in the proper context. Data derives from focus group interviews with child welfare workers from Norway, Lithuania, Chile and England based on discussions of a common fictitious complex family case (vignette). The four countries chosen for this comparative study are examples of four different welfare systems/regimes. The findings related to this broad area of caring topics are related to how the dimensions of a ‘private’ and a ‘public’ family manifest in social work in the four countries. Social workers in Chile and Lithuania refer to the idea of the private family, while their Norwegian counterparts lean more to the public family. English social workers combine public and private family conceptions in their focus groups, reflecting a system that is partly de-familialized.SpanishFamilias públicas y privadas. La visión de los trabajadores sociales sobre la posición de hijos y padres en Chile, Inglaterra, Lituania y Noruega.Los trabajadores sociales en todo el mundo lidian con familias y sus complejidades en su práctica cotidiana. En este estudio de comparación internacional exploramos las prácticas de intervención en familias de trabajadores sociales en relación con sus definiciones y funciones, así como los modos en que los trabajadores sociales equilibran los derechos de padres e hijos y las políticas sociales en el contexto apropiado. Los datos provienen de entrevistas grupales con trabajadores sociales de servicios de bienestar infantil en Noruega, Lituania, Chile e Inglaterra, basadas en la discusión acerca de un caso común ficticio de familia compleja (viñeta).  Los cuatro países seleccionados para este estudio comparativo ejemplifican cuatro regímenes o sistemas de bienestar. Los resultados relativos a esta amplia área del tema del cuidado tienen que ver con cómo las dimensiones de “familia privada” y “familia pública” se manifiestan en el trabajo social de estos cuatro países. Los trabajadores sociales de Chile y Lituania hacen referencia a la idea de la familia privada, mientras sus colegas noruegos se inclinan más hacia la familia pública. Los trabajadores sociales ingleses apuntan hacia una combinación de las concepciones de familia pública y privada en sus grupos focales, reflejando un sistema que es parcialmente de-familiarizado.